2019
DOI: 10.1002/dmrr.3219
|View full text |Cite
|
Sign up to set email alerts
|

Glyco‐metabolic control, inflammation markers, and cardiovascular outcomes in type 1 and type 2 diabetic patients on insulin pump or multiple daily injection (italico study)

Abstract: Background: To evaluate if the positive effects recorded on glycaemic control with continuous subcutaneous insulin infusion (CSII) were maintained on the long-term compared with multiple daily injection (MDI). The secondary objective was to evaluate if there is a reduction of type and number of cardiovascular events (CV).Methods: This retrospective, observational study evaluated glycaemic control and the number of CV in 104 patients with type 1 or 2 diabetes previously treated with MDI and initiating CSII ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In view of the difficulties in the CVD risk prediction in T1D, 43 in which tools like CVD risk scores perform rather poorly 43,44 or are not well‐validated, 45 the evaluation of preclinical atherosclerosis or the use of non‐classical CVD risk factors (such as IR markers) are a promising approach in the identification of individuals at the highest risk. Due to the growing prevalence of obesity in T1D, 35 eGDR could emerge as a chief non‐glycaemic variable for the early detection of patients in whom intensive treatment (either cardioprotective or glucose‐lowering 7 ) is warranted in order to tackle the main cause of mortality among this population 1,3,6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the difficulties in the CVD risk prediction in T1D, 43 in which tools like CVD risk scores perform rather poorly 43,44 or are not well‐validated, 45 the evaluation of preclinical atherosclerosis or the use of non‐classical CVD risk factors (such as IR markers) are a promising approach in the identification of individuals at the highest risk. Due to the growing prevalence of obesity in T1D, 35 eGDR could emerge as a chief non‐glycaemic variable for the early detection of patients in whom intensive treatment (either cardioprotective or glucose‐lowering 7 ) is warranted in order to tackle the main cause of mortality among this population 1,3,6 …”
Section: Discussionmentioning
confidence: 99%
“…3 Thus, other general and T1D-related variables such as body mass index (BMI), lipid parameters, blood pressure (BP), smoking status, diabetes duration, continuous subcutaneous insulin infusion [CSII] use, albumin excretion rate, diabetic retinopathy and more recently, even glycaemic variability have been linked to CVD in this specific group. [4][5][6][7][8] Furthermore, although impaired insulin sensitivity is regarded as the cornerstone of type 2 diabetes (T2D), 9 it can also be a feature in some patients with T1D ('double diabetes'). 10 From this perspective, insulin resistance (IR) markers have emerged as an additional and significant CVD risk factor in the assessment of chronic vascular complications and mortality in the T1D population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory cytokines can inhibit the secretion of gonadotropin-releasing hormones, thereby reducing the level of circulating luteinizing hormone in vivo and in vitro (20), indicating that a proinflammatory state may contribute to the central inhibition of the male sex axis. Intensive insulin therapy can reduce the inflammatory response (21). Previous studies have also found that short-term intensive therapy for 5 days can significantly increase the level of testosterone (15).…”
Section: Discussionmentioning
confidence: 97%
“…A 12-month, randomized, multicenter case–control study found that PwD using insulin pumps demonstrated increased HDL-C and decreased total cholesterol, LDL-C, and triglycerides as compared to MDI users. This finding persisted after 8 years of follow-up [ 56 , 125 ]. During the follow-up study, CSII use was also associated with fewer cardiovascular events, specifically atrial fibrillation, premature ventricular contractions, acute coronary infarction, angina pectoris, peripheral vascular ischemia, and heart failure, as compared to MDI use [ 125 ].…”
Section: Diabetes Technology and Cardiovascular Outcomesmentioning
confidence: 99%